I believe my question is relatively easy but I'm not sure why I can't comprehend the concept anymore.

Given the equation, which models the population:


Obtain the solution of the differential equation with inital condition $N(0)=2$, assuming parameters $c=1$ and $k=\frac{1}{2}$.

So just inputting the parameters our equation becomes:

$\frac{dN}{dt}= N(N-\frac{1}{2})(1-N)$, $N(0)=2$.

So my first thought was separable equation but the differential with respect to $t$ is confusing me.

Is it the right method to turn it in to:

$\frac{1}{N(N-\frac{1}{2})(1-N)} dN = 1 dt$ and then continue on wards.

Or am I supposed to be getting the following:

$N(N-\frac{1}{2})(1-N) dt = 1 dN $

My instinct tells me it must be the first method but then I have no idea how I could integrate that function.

Any help/hints would be appreciated.


My personal attempt was as follows: $\int\frac{1}{N(N-\frac{1}{2})(1-N)} dN =\int 1 dt$

Taking partial fractions of the left side we get:

$-\int \frac{2}{N} dN + \int \frac{8}{2N-1}dN-\int\frac{2}{N-1} dN = \int 1dt$

This then leads us to: $-2ln\lvert N\rvert +4ln\lvert 2N-1\rvert-2ln\lvert N-1\rvert = t + C $

And after taking the initial condition $N(0)=2$ we find $C = 3$ hence the final equation should be as follows:

$-2ln\lvert N\rvert +4ln\lvert 2N-1\rvert-2ln\lvert N-1\rvert -3 = t $

However the question gave a hint regarding finding a quartic equation for $N$ which I did not find with my method so this leads me to believe there is an error of some sort with my method.

  • $\begingroup$ How did you obtain $\dfrac{dN}{dt}= N(N-\frac{1}{2})(1-N)$. $\endgroup$ – Nosrati Feb 22 '17 at 12:40
  • $\begingroup$ @MyGlasses just using the parameters given of $c=1, k=\frac{1}{2}$ $\endgroup$ – Evan Feb 22 '17 at 12:44
  • $\begingroup$ hahaha. You changed the equation! $\endgroup$ – Nosrati Feb 22 '17 at 12:46
  • $\begingroup$ Just one n -> N :) $\endgroup$ – Evan Feb 22 '17 at 12:49
  • $\begingroup$ Well. Separate fractions in $\dfrac{1}{N(N-\frac{1}{2})(1-N)} dN = 1 dt$ $\endgroup$ – Nosrati Feb 22 '17 at 12:50

Well, this is a separable equation:

$$\mathscr{N}'\left(t\right)=\text{c}\cdot\left(\mathscr{N}\left(t\right)-\text{k}\right)\cdot\left(1-\mathscr{N}\left(t\right)\right)\space\Longleftrightarrow$$ $$-\int\frac{\mathscr{N}'\left(t\right)}{\mathscr{N}\left(t\right)\cdot\left(\mathscr{N}\left(t\right)-1\right)\cdot\left(\mathscr{N}\left(t\right)-\text{k}\right)}\space\text{d}t=\int\text{c}\space\text{d}t\tag1$$

Now, we can use:

  • Substitute $\text{u}=\mathscr{N}\left(t\right)$: $$-\int\frac{\mathscr{N}'\left(t\right)}{\mathscr{N}\left(t\right)\cdot\left(\mathscr{N}\left(t\right)-1\right)\cdot\left(\mathscr{N}\left(t\right)-\text{k}\right)}\space\text{d}t=-\int\frac{1}{\text{u}\cdot\left(\text{u}-1\right)\cdot\left(\text{u}-\text{k}\right)}\space\text{d}\text{u}\tag2$$
  • $$\int\text{c}\space\text{d}t=\text{c}\int1\space\text{d}t=\text{c}\cdot t+\text{K}=\text{K}+\text{c}t\tag3$$

Now, for the $\text{u}$ integral, use partial fractions:


  • 1
    $\begingroup$ Nice answer, but why the fancy $N$? $\endgroup$ – Bobson Dugnutt Feb 24 '17 at 13:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.